The Effect of Fraud Hexagon on the Potential of Fraudulent Financial Statements with Islamic Corporate Governance as a Moderation: A Study on Indonesian and Malaysian Sharia Banking - Firdaus, Fatimah Azzahra; Burhany , Dian Imanina; Rohendi , Hendi (Cv. Syntax Corporation Indonesia, 2026)
This research analyzes the influence of the Fraud Hexagon on fraudulent financial statements with Islamic Corporate Governance (ICG) as a moderator in Islamic banking in Indonesia and Malaysia, motivated by the potential for financial statement fraud in the industry despite Sharia principles emphasizing honesty and accountability. Performance pressure, weak oversight, and transaction complexity necessitate empirical testing using the Fraud Hexagon Theory approach. This research used a quantitative approach with explanatory research. The sample includes Islamic commercial banks in Indonesia and Malaysia, selected using purposive sampling based on the availability of financial and annual reports for the 2015-2024 period, yielding 140 observations for Indonesia and 150 for Malaysia. The data is secondary data organized in a panel structure and analyzed using moderated regression analysis with EViews 12. Model estimation used the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), selected based on the Chow, Hausman, and Lagrange Multiplier tests. The results show that the factors influencing fraudulent financial statements differ between the two countries, and Islamic Corporate Governance is proven to moderate part of that influence, particularly the financial stability dimension. This study is expected to contribute theoretically to the development of the Fraud Hexagon and Islamic Corporate Governance literature, as well as practically for management, regulators, and stakeholders in improving governance quality and minimizing fraudulent financial statement risk in Indonesia and Malaysia.